The influence of ownership structure on the firms dividend policy based on lintner model / Norhasniza Mohd Hasan Abdullah, Zuraidah Ahmad and Shashazrina Roslan - Mohd Hasan Abdullah, Norhasniza; Ahmad, Zuraidah; Roslan, Shashazrina (2012)
This study investigates the relationship between types of ownership structure and dividend payments of Malaysian listed companies. A cross-sectional analysis of 100 sample firms listed on the main board of Bursa Malaysia for the years 2010 is utilized. The study examines the explanatory power of two alternative models of dividend policy, the full adjustment model and the partial adjustment model modified which are moderated by the possible effects of five types of ownership structure, namely ownership concentration, ownership dispersion, institutional ownership, managerial ownership and foreign ownership. Ownership concentration is measured by the Herfindahl Index while ownership dispersion is measured by ratio of the number of shareholders to total outstanding shares. Institutional ownership is measured by a percentage of equity owned by institutional investors, while, managerial ownership is measured by adding the total percentage of shares directly held by non independent executive directors in the company, and foreign ownership is measured by the sum of all shares in the hands of foreign shareholders in the list of thirty largest shareholders, either held through nominee companies or other corporate foreign share holdings. Ownership concentration variables are found to be positively and statistically significant in influencing dividends in every type of dividend model. The finding is consistent with agency theory since high dividend payments can be used for mitigating agency conflict as dividends can be substituted for shareholder monitoring. Hence, large shareholders have strong incentives to require higher dividend payments in order to reduce monitoring costs. Nevertheless, this study shows that dividend decisions of Malaysian companies are not influenced by the structure of ownership.